Factors Associated with Interest in Complementary and Alternative Medicine Among Young Adult Survivors of Childhood Cancer. (January 2022) - Baron Nelson, Mary; Kim, Yoonji; Hamilton, Lauren; Dekker, Anneke; Miller, Kimberly; Hamilton, Ann S.; Milam, Joel
Background: Use of complementary and alternative medicine (CAM) by those undergoing cancer treatment is common. While some childhood cancer survivors (CCS) may use CAM to treat late effects, others may lack information about available alternative therapies. We sought to determine characteristics associated with seeking more information about CAM among an ethnically diverse sample of young adult CCS.Methods: Young adult CCS were selected from the population-based Los Angeles SEER cancer registry and surveyed at ages 18 to 39 as part of the Project Forward Cohort. Associations between demographic, clinical, and other factors with seeking information on CAM were examined with t-tests, Chi Square analyses, and logistic regression.Results: Among 1106 participants surveyed, 182 (18%) reported interest in obtaining more information on CAM. Interest in CAM was highest among males, older (vs. younger) participants, those born outside the U.S., those with a history of relapsed/recurrent or second cancers, those with greater depressive symptoms, and those with poorer self-rated health. Among Hispanic/Latino/Latinx respondents, depressive symptoms, birth outside the U.S., and higher Latino culture orientation was positively associated with CAM interest.Discussion: Depressive symptoms and unresolved health problems are associated with a need for information about alternative forms of therapy, particularly in those with born outside the U.S. Healthcare providers caring for CCS can incorporate appropriate CAM information to help address unmet physical and mental health needs.